Enhancing Photoelectric Conversion Efficiency of Solar Panel by Water Cooling - M Mohamed Musthafa (Institute of Advanced Engineering and Science, 2014)
Photovoltaic solar cell generates electricity by receiving solar irradiance. The electrical efficiency of photovoltaic (PV) cell is adversely affected by the significant increase of cell operating temperature during absorption of solar radiation. This undesirable effect can be partially avoided by cooling the back side of the photovoltaic panel using water absorption sponge which was fixed on of PV panel and maintain wet condition by circulation of drop by drop water. The objective of the present work is to reduce the temperature of the solar cell in order to increase its electrical efficiency. Experiments were performed with and without water cooling. A linear trend between the efficiency and temperature was found. Without cooling, the temperature of the panel was high and solar cells were achieved an efficiency of 8–9%. However, when the panel was operated under water cooling condition, the temperature dropped maximally by 40C leading to an increase in efficiency of solar cells by 12%.